Comparative Phytochemical Analysis and Antimicrobial Properties of Ethanol and Macerated Extracts from Aerial and Root Parts of Achillea nobilis - Aiman Berdgaleeva; Zere Zhalimova; Akzharkyn Saginbazarova; Gulbanu Tulegenova; Dana Zharylkassynova; Aliya Bazargaliyeva; Zhaidargul Kuanbay; Svetlana Sakhanova; Akmaral Ramazanova; Akzhamal Bilkenova; Aigul Sartayeva (Molecules, 2025)
Achillea nobilis represents a species of considerable medicinal importance within the Asteraceae family, historically employed in Central Asia and various Eurasian territories for the management of inflammatory, microbial, and gastrointestinal ailments. Notwithstanding its extensive ethnopharmacological significance, the phytochemical profile and pharmacological attributes of its various anatomical components have not been comprehensively investigated. This research endeavor sought to delineate the phytochemical constituents and evaluate the antimicrobial efficacy of ethanol extracts derived from both the aerial and root segments of A. nobilis. Qualitative phytochemical analysis and GC–MS characterization unveiled a diverse array of bioactive compounds, encompassing flavonoids, phenolic compounds, organic acids, lactones, alcohols, and heterocyclic derivatives. In particular, the aerial oil extract exhibited the presence of terpenoids, fatty acids and their esters, sterols, hydrocarbons, and minor organosilicon and cyclobutanone derivatives, with notable compounds such as linoleic acid (8.08%), 6-tetradecyne (14.99%), isopropyl linoleate (14.64%), and E,Z-1,3,12-nonadecatriene (22.25%). In vitro antimicrobial activity was assessed against eight clinically relevant microbial strains employing the broth microdilution technique. The aerial ethanol extract exhibited pronounced antimicrobial properties, particularly against MRSA and C. albicans, with MICs ranging from 0.5 to 2 mg/mL, whereas the root ethanol extract displayed MICs of 1 to 3 mg/mL. Additionally, the aerial oil extract showed moderate inhibitory activity, with MIC values ranging from 1.5 to 3 mg/mL, demonstrating effectiveness particularly against C. albicans, C. neoformans, and MRSA. These findings underscore the therapeutic potential of A. nobilis, particularly its aerial component, as a viable natural source of antimicrobial agents.